Oropouche fever: An emerging arbovirus disease from the Americas with possible oral manifestations - Rocha , Breno Amaral; Souto , Giovanna Ribeiro; Grossmann, Soraya de Mattos Camargo; Souza , Paulo Eduardo Alencar; Soares , Rodrigo Villamarim; Horta, Martinho Campolina Rebello (Journal of Oral Diagnosis, 2024)
Oropouche fever (OROV fever) is an emerging arbovirus disease caused by Oropouche virus (OROV). The virus was reported to have a limited circulation in Central and South America, but there is a real possibility of international spread in the near future. Considering the current outbreak of OROV fever in the Americas, the Pan American Health Organization/World Health Organization has already published one Epidemiological Alert and two Epidemiological Updates in 2024. From January to early October 2024, 10,275 cases were confirmed in nine American countries, including imported cases in the United States and Canada. Moreover, 30 imported cases were reported for the first time in three European countries. Knowledge about OROV fever is still limited. Like common arbovirus diseases, the main clinical manifestations include fever, headache, arthralgia, myalgia, bleeding and rash. Gingival bleeding has been reported, and oral mucosal lesions may be another possible manifestation. The disease is usually mild and self-limiting, but severe complications, death and vertical transmission can occur. This article reviews OROV fever, addressing possible oral manifestations as well as the potential contribution of the dental community to prompt diagnosis and management.